Two-dimensional growth, anisotropic polaron transport and magnetic phase segregation in epitaxial Nd₀.₅₂Sr₀.₄₈MnO₃ films - Prokhorov, V.G.; Kaminsky, G.G.; Kim, J.M.; Eom, T.W.; Park, J.S.; Lee, Y.P.; Svetchnikov, V.L.; Levtchenko, G.G.; Paschenko, A.V.; Medvedev, Yu.V.; Nikolaenko, Yu.M.; Bukin, G.V.; et al. (Физика низких температур, 2011)
Nd₀.₅₂Sr₀.₄₈MnO₃ films have been prepared by dc magnetron sputtering on LaAlO₃ (001) and SrTiO₃ (011) single-crystalline substrates with an additional annealing for the lattice strain relaxation. Even though that the Nd₀.₅₂Sr₀.₄₈MnO₃ films were deposited simultaneously on different substrates at the same deposition rate they differ in the thickness by≃2 . The observed difference in the thickness is explained by the twodimensional (layer-by-layer) growth of film rather than a difference in the growth rate, controlled by the crystal orientation of substrate. The analysis of the optical and transport properties reveals that the observed anisotropy in the polaron motion is governed by a strong anisotropy of the trapping energy rather than the polaron formation one. It was shown that the deposited Nd₀.₅₂Sr₀.₄₈MnO₃ films manifest a magnetic behavior typical for twophases magnetic systems and must be considered as an assembly of interacting magnetic clusters.